Business basics : workbook - Grant, David. (Oxford University Press, 1995)
You and your company. Preparing a trip. Away on business. Visiting a company. New developments. Arrangements. Describing and comparing. Success stories. Dealing with problems. People at work. Getting a job. Working in the nineties.